The Flare of Rheumatic Disease After SARS-CoV-2 Vaccination: A Review - Xie, Yan; Liu, Yang; Liu, Yi (Frontiers in Immunology, 2022)
As the coronavirus disease 2019 (COVID-19) pandemic continues, rheumatic disease (RD) patients are strongly recommended to receive vaccination against the acute respiratory syndrome coronavirus 2（SARS-CoV-2）due to the increased risk of infection and more severe outcomes of COVID-19 in these patients. However, concern for the induction of RD flare may combat the enthusiasm for vaccination. For RD patients, current pieces of evidence don’t support for increased risk of disease flare after COVID-19 vaccination. However, the disease flare of RDs may be triggered by COVID-19 vaccination, especially for patients with high disease activity. Most of these flares after vaccination are mild and need no treatment escalation. Considering the benefit and risks, RD patients are recommended to receive the COVID-19 vaccination but should be vaccinated when the RDs are in a stable state.